Implementasi Sistem Pembelajaran Pendidikan Agama Islam Pada Perguruan Tinggi Umum (Studi Kasus di STKIP Pasundan Bandung) - Yudha Al Farisi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research describes the implementation of Islamic teaching at STKIP Pasundan Bandung. This research method uses. This type of research uses descriptive. Primary data sources, heads of higher education institutions, lecturers and students. Secondary data sources, books, research journals and websites. Data collection techniques used, interview observation and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The findings are as follows. First, Islamic teaching materials at STKIP Pasundan consist of main topics and several others developed to meet student characteristics. Second, the special competencies needed are the unity of God, character, and problem solving. Third, the strategies used by teachers are flexibility of class rules, providing models, and contextual teaching and fourth, evaluation, especially affective evaluation.